Ambient assisted living : ICT-based solutions in real life situations : 7th International Work-Conference, IWAAL 2015, Puerto Varas, Chile, December 1-4, 2015 : proceedings /: ICT-based solutions in real life situations : 7th International Work-Conference, IWAAL 2015, Puerto Varas, Chile, December 1-4, 2015 : proceedings. ([2015]) - Unknown
No abstract available